Bimbingan Teknis Pembelajaran Daring SD Muhammadiyah Muara Jawa Tahun Pembelajaran 2020/2021 - Nur Agus Salim (Jurnal Pengabdian Ahmad Yani, 2021)
During the Covid-19 pandemic, schools continue to carry out online learning. The purpose of the implementation of this service is to provide understanding to schools and teachers in the implementation of online learning and to guide teachers in online learning practices. The method of implementing PPM activities is carried out in the form of training including Lectures. The lecture method is used to deliver material about online learning, and the types of applications that can be used in the implementation of online learning. The practical method is used to independently practice online learning applications in schools. The next method is to ask questions, share, and practice mentoring.